2013
DOI: 10.1002/cncr.28204
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 trial of intravenous and intraperitoneal paclitaxel combined with S‐1 for treatment of gastric cancer with macroscopic peritoneal metastasis

Abstract: BACKGROUND:The prognosis of patients with gastric cancer with peritoneal metastasis is extremely poor. This phase 2 study evaluated the benefits and tolerability of weekly intravenous and intraperitoneal paclitaxel (PTX) treatment combined with oral S-1 in patients with gastric cancer who had macroscopic peritoneal metastasis. METHODS: Patients with gastric cancer who had primary tumors with macroscopic peritoneal metastasis were enrolled. PTX was administered intravenously at 50 mg/m 2 and intraperitoneally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 17 publications
2
104
1
Order By: Relevance
“…Additionally, S-1 is one of the oral 5-FU agents that were found to be non-inferior to gemcitabine in terms of overall survival in East-Asian patients with metastatic pancreatic cancer (3). Yamaguchi et al reported that IV and IP PTX with S-1 was well tolerated and highly effective against peritoneal metastases from gastric cancer (5), and the MPACT trial demonstrated that PTX was effective in metastatic pancreatic cancer (4). In fact, IV and IP PTX with S-1 recently exhibited promising results in gemcitabine-refractory pancreatic cancer (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, S-1 is one of the oral 5-FU agents that were found to be non-inferior to gemcitabine in terms of overall survival in East-Asian patients with metastatic pancreatic cancer (3). Yamaguchi et al reported that IV and IP PTX with S-1 was well tolerated and highly effective against peritoneal metastases from gastric cancer (5), and the MPACT trial demonstrated that PTX was effective in metastatic pancreatic cancer (4). In fact, IV and IP PTX with S-1 recently exhibited promising results in gemcitabine-refractory pancreatic cancer (6).…”
Section: Discussionmentioning
confidence: 99%
“…S-1, an oral 5-fluorouracil (5-FU) derivative and paclitaxel (PTX) have been proven to be effective in the treatment of metastatic pancreatic cancer (3,4). Combination chemotherapy consisting of intravenous (IV) and intraperitoneal (IP) PTX with S-1 was well-tolerated and achieved promising results against peritoneal metastases from gastric and pancreatic cancer (5,6). However, to the best of our knowledge, a conversion of an unresectable pancreatic cancer with peritoneal metastases to a resectable one by this combination chemotherapy has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Grade histological response of peritoneal cytology or small PC, to offer conversion to resectability of the selected patients but also to improve overall survival in patients with an initial PCI ≥ 20 [23].…”
Section: Toxicitymentioning
confidence: 99%
“…Intraperitoneal regimens are administered in the adjuvant setting for ovarian cancer [12,13] and in the neoadjuvant setting for gastric cancer [14][15][16][17][18][19][20][21][22][23][24][25]. A similar evolution of peritoneal and hepatic metastases of colorectal origin was shown recently by a French group [26] but, while multiple non-optimally resectable hepatic metastases benefit from a local chemotherapy using an hepatic arterial infusion, no similar approach was proposed for PC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, taxanes, such as paclitaxel (PTX) or docetaxel (DOC), are supposed to be ideal drugs for IP chemotherapy because of high local concentrations over a long period of time due to their hydrophobic properties [10]. In fact, we and others have recently shown that IP administration of PTX or DOC can exhibit remarkable effects against PM from gastric cancer (GC) [11][12][13][14]. However, the underlying mechanism to explain the marked shrinkage of PM is still unknown.…”
Section: Introductionmentioning
confidence: 99%